2016
DOI: 10.1186/s40425-016-0156-7
|View full text |Cite
|
Sign up to set email alerts
|

Current clinical trials testing the combination of immunotherapy with radiotherapy

Abstract: Increasing evidence demonstrates that radiation acts as an immune stimulus, recruiting immune mediators that enable anti-tumor responses within and outside the radiation field. There has been a rapid expansion in the number of clinical trials harnessing radiation to enhance antitumor immunity. If positive, results of these trials will lead to a paradigm shift in the use of radiotherapy. In this review, we discuss the rationale for trials combining radiation with various immunotherapies, provide an update of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
286
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 334 publications
(290 citation statements)
references
References 93 publications
(98 reference statements)
3
286
1
Order By: Relevance
“…10 Combination of radiation and various immunotherapies have been under investigation in the clinic. 11 Among immune intervention therapies, interleukin-12 (IL-12) is considered as the most potent cytokine in triggering antitumor immune responses. 12,13 IL-12 is critical in the activation of innate immunity, including antigen-presenting activity of DCs, and subsequent activation of T-helper 1 cell (Th1) immunity, and in promoting the killing function of cytotoxic T lymphocytes and natural killer cells.…”
Section: Introductionmentioning
confidence: 99%
“…10 Combination of radiation and various immunotherapies have been under investigation in the clinic. 11 Among immune intervention therapies, interleukin-12 (IL-12) is considered as the most potent cytokine in triggering antitumor immune responses. 12,13 IL-12 is critical in the activation of innate immunity, including antigen-presenting activity of DCs, and subsequent activation of T-helper 1 cell (Th1) immunity, and in promoting the killing function of cytotoxic T lymphocytes and natural killer cells.…”
Section: Introductionmentioning
confidence: 99%
“…Platinum is used widely in chemotherapeutics of NSCLC [69,70]. Platinum-based chemotherapy and targeted therapies are milestones in lung cancer treatment [71,72].…”
Section: Lncrnas Radiochemotherapy In Nsclcmentioning
confidence: 99%
“…Radiation affects the immune system in many ways including release of neoantigens, upregulation of PD-L1 on tumor cells, recruitment of T cells to the tumor bed and neutralization of the immune-suppressive effects of the tumor microenvironment. Over 60% of patients with NSCLC require radiotherapy at least once during their course of treatment, and radiotherapy used in combination with immune checkpoint blockade has shown potential in preclinical and early clinical studies [3,6,7,18]. A Phase II trial of consolidation pembrolizumab initiated 1-2 months after concurrent chemoradiation demonstrated safety of such treatment [19].…”
mentioning
confidence: 99%
“…By activating the immune system to recognize and eliminate cancer, immune checkpoint blockade has the potential to elicit durable responses and augment survival outcomes for a subset of patients [1,2]. In addition, the ability of radiotherapy to induce an immunogenic response and neutralize the immune-suppressive effects of the tumor microenvironment, uniquely positions it as a synergistic tool at the center of emerging multimodal therapies utilizing immune checkpoint blockade [3][4][5][6][7].Immune checkpoint inhibitors of the PD-1/PD-L1 pathway have emerged as a promising new therapeutic strategy [8][9][10][11]. These agents have produced durable clinical responses and antitumor activity in Phase I trials, leading to subsequent randomized Phase II and III trials that demonstrated significant improvements in overall survival when compared with cytotoxic chemotherapy alone [12][13][14][15][16].…”
mentioning
confidence: 99%
See 1 more Smart Citation